2021
DOI: 10.2478/rjim-2020-0038
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal endoscopic practice during COVID-19 pandemic: a multi-institutional survey

Abstract: Introduction: An on-going coronavirus disease 2019 (COVID-19) has become a challenge all over the world. Since an endoscopy unit and its staff are at potentially high risk for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, we conducted a survey for the management of the gastrointestinal endoscopic practice, personal protective equipment (PPE), and risk assessment for COVID-19 during the pandemic at multiple facilities.Methods: The 11-item survey questionnaire was sent to representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
3
13
1
1
Order By: Relevance
“…During the COVID-19 pandemic era, opportunities for cancer screening by upper gastrointestinal endoscopy (UGI) or colonoscopy may have decreased because it is an aerosol-generating procedure [ 23 ]. In fact, it was reported that the total volume of endoscopic procedures decreased by 44% during this time [ 24 ]. The decline in the number of gastrectomies or anterior resections of the rectum may be related to the decrease in these endoscopic screening procedures.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic era, opportunities for cancer screening by upper gastrointestinal endoscopy (UGI) or colonoscopy may have decreased because it is an aerosol-generating procedure [ 23 ]. In fact, it was reported that the total volume of endoscopic procedures decreased by 44% during this time [ 24 ]. The decline in the number of gastrectomies or anterior resections of the rectum may be related to the decrease in these endoscopic screening procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with IBD, lifestyle factors, such as smoking or drug adherence, and psychological stresses were reported to significantly influence the disease activity [ 102 , 103 , 104 , 105 ]. The pandemic and lockdown also resulted in reduced access to face-to-face outpatient clinics for IBD patients and diagnostic examinations, such as endoscopy [ 106 , 107 ]. Taken together, the pandemic and lockdown would change patients’ symptoms and the clinical course of IBD.…”
Section: Human Herpesviruses In the Era Of Covid-19mentioning
confidence: 99%
“…6,7 Therefore, screening upper gastrointestinal (GI) endoscopy tends to be postponed, especially during the outbreak period. 8 After the first outbreak in Japan, in accordance with a novel infection control policy, screening upper GI endoscopy has gradually become available on a regular basis due to the importance of early detection of GI cancers. However, many patients infected with SARS-CoV-2 are prevalent in society.…”
Section: Introductionmentioning
confidence: 99%